Pengaruh Lingkungan Sekolah Dan Komunikasi Interpersonal Terhadap Kreativitas Guru PNS Di SDN Teluk Pucung Bekasi Utara - An Nisaa’ Shabrina; Tungga Buana Irfana; Supriyanto Supriyanto; Djuni Thamrin; Matdio Siahaan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of the school environment and interpersonal communication on the creativity of civil servant teachers at SDN Teluk Pucung, North Bekasi. This type of research is quantitative and the data analysis used is classical assumption testing and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 27 application. Partially the training variable influences teacher creativity with t-count < t-table . Based on the test results and data analysis, partial test calculation results were obtained which showed that the calculated t value > t table (2.798 > 2.039) with a significance value of 0.009 < 0.05. Partially, the School Environment variable has a positive influence on teacher creativity with a t-value < t-table. Based on the test results and data analysis, partial calculation results were obtained which showed a value of 3.177 (t-count) > 2.039 (t-table) with a significance value of 0.003 < 0.05. Meanwhile, based on the simultaneous test results obtained from this research, the communication and work discipline variables have obtained a value of 22.329 (calculated f) > 3.30 (table f).